PENGARUH LEVERAGE DAN PROFITABILITAS TERHADAP KEBIJAKAN DEVIDEN (GEMA EKONOMI, 2022)
The Objective to evaluate the effect of debt to equity ratio, return on assets, and net profit margin on dividend payout ratio. The research was on manufacturing companies operating in the food and beverage subsector listed on the Indonesia Stock Exchange between 2017 and 2020. The sampling methodology used in this study is a quantitative approach, with multiple linear regression analysis. (1) The use of statistical analysis through t-tests shows that the debt to equity ratio has a real and partially beneficial effect on the dividend payout ratio. Nonetheless, it should be noted that the dividend payout ratio is not significantly affected by the return on assets and net profit margin. (2) The use of statistical analysis through the F-test is used for statistical analysis, the effect of debt to equity ratio, return on assets, and net profit margin on dividend payout ratio.